The Immunohistochemistry Profile of Lymphocytic Gastritis in Celiac Disease and Helicobacter Pylori Infection: Interplay between Infection and Inflammation - Efrat Broide; Judith Sandbank; Eitan Scapa; Nimrod Alain Kimchi; Michael Shapiro; Aaron Lerner (Mediators of Inflammation)
Lymphocytic gastritis (LG) is associated with helicobacter pylori (Hp) and celiac disease (CD). We aimed to clarify the relationship between Hp infection and CD by defining a unique histopathology profile of LG in these two diseases. Forty patients who underwent upper endoscopy were divided into four groups: eight controls, ten active CD patients without Hp, twelve CD negative with Hp, and ten active CD with Hp infection. Antral samples were assessed by immunohistochemical staining for CD20, CD3, CD4, CD8, CD57, CNA42, and Ki67 for lymphoid aggregates, intraepithelial lymphocytes (IELs) number, density of lamina propria (LP) lymphocytes, and inflammatory glandular involvement. Only IELs positive for CD3 and CD8 were increased significantly in CD patients with or without Hp infection. Hp did not contribute to the number of CD8 IELs. In complicated cases with Hp and suspicious for CD, the number of CD8+ IELs hints toward a CD rather than Hp infection.